A comparison of the severity of reproductive failure between single and dual infection with porcine reproductive and respiratory syndrome virus (PRRSV)‐1 and PRRSV‐2 in late‐term pregnancy gilts. Issue 6 (7th June 2018) - Jeong, Jiwoon; Kang, Ikjae; Park, Changhoon; Kim, Seeun; Park, Su‐Jin; Park, Kee Hwan; Oh, Taehwan; Yang, Siyeon; Yoon, Jai Soon; Lee, Ohhyung; Chae, Chanhee
Abstract: The objective of this study was to compare the severity of reproductive failure caused by either a single or a dual infection with porcine reproductive and respiratory syndrome virus (PRRSV)‐1 and PRRSV‐2 in late‐term pregnancy gilts. Pregnant gilts were intranasally administered PRRSV‐1, PRRSV‐2 or both at 3 weeks before the expected farrowing date (93 days of gestation). Regardless of single and dual infection, PRRSV‐infected pregnant gilts experienced premature farrowing (103–109 days of gestation) compared with negative control gilts which carried their pregnancy to full term (114–115 days of gestation). Pregnant gilts infected with only PRRSV‐1 had a significantly ( p < 0.05) higher number of genomic copies of PRRSV‐1 in their blood compared with dually infected gilts. Additionally, stillborn foetuses and live‐born piglets from pregnant gilts infected with only PRRSV‐1 had a significantly ( p < 0.05) higher number of PRRSV‐1‐positive cells per unit area of tissue sections examined, compared to pregnant gilts dually infected with PRRSV‐1 and PRRSV‐2. In contrast, pregnant gilts infected with only PRRSV‐2 showed no difference in the number of genomic copies of PRRSV‐2 compared with dually infected pregnant gilts and there were no significant differences in PRRSV‐2‐positive cells per unit area in tissues of stillborn foetuses and live‐born piglets from pregnant gilts infected with PRRSV‐2 only compared with dually infected gilts. Interestingly, even though PRRSV‐2 was shown to replicate more efficiently compared with PRRSV‐1 in dually infected pregnant gilts, neither PRRSV type was able to exacerbate reproductive failure in pregnant gilts already dually infected with PRRSV‐1 and PRRSV‐2. Our results suggest that the severity of reproductive failure is similar between dual (PRRSV‐1 and PRRSV‐2) and single infection (PRRSV‐1 or PRRSV‐2).